HADIS-HADIS KONTRADIKTIF:‎LARANGAN DAN KEBOLEHAN PENULISAN HADIS - Juli Julaiha Pulungan; Tutia Rahmi; Khairin Nazmi (Al-Thiqah: Journal of Hadith and Prophetic Tradition, 2024)
The hadiths of Prophet Muhammad (SAW) are the primary source of Islamic teachings after the Qur'an, serving as a guide for Muslims. However, throughout history, contradictions have emerged among various hadiths, leading to debates regarding their authenticity, interpretation, and validity. One of the main issues of discussion is the prohibition and permissibility of writing hadiths. In the early period of Islam, the recording of hadiths was strictly limited, even prohibited, to prevent any distortion or deviation from the pure teachings of Islam. Over time, the documentation of hadiths was allowed under strict conditions and procedures to prevent the spread of fabricated hadiths. The debate over this prohibition and permissibility reflects the Muslim community's effort to preserve the authenticity of the Prophet's teachings while also facing challenges in verifying and filtering contradictory hadiths. This abstract discusses the background, factors contributing to the emergence of contradictory hadiths, and the historical and scholarly developments surrounding the prohibition and permissibility of hadith documentation. This study aims to provide a deeper understanding of the complexity of contradictory hadiths and their implications for religious practices and the advancement of hadith studies.